SIKAP MAHASISWA UNIVERSITAS NEGERI YOGYAKARTA TERHADAP KEPEMIMPINAN WANITA - MUHYADI MUHYADI (Universitas Negeri Yogyakarta, 2004)
Abstract University students are specific group of educated community; and therefore have a better way in thinking and responding the stimuli coming to them. They are relatively free from vested interests so that their thinking system and attitude toward community and state problems are usually objectives. The same attitude also appears when they are faced with gender problems especially female leaderships. The subjects of this study are the students of the State University of Yogyakarta (UNY). This research aims at revealing the UNY students’ attitude (which is shaped through educational process) toward female leaderships. The findings of the research show that: (1) more than 60% the students have positive attitude toward female leadership (2) more than 60% of the students believe that women will be successful in leading an organization if they are given the opportunity to do the job (3) more than 60% students believe that managerial skills are more important than sexes in determining the success of a leader (4) more than 60% of the students have the opinion that to be a successful woman leader, one should graduate from a senior high school or a higher educational institute (5) more than 60% of the students agree on the appointment of a women as a state leader (7) the students acceptance of a female leader is not significantly affected by her gender or religion. Keywords: students, attitude, female leadership